2020
DOI: 10.1515/nleng-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetized variable thermal conductivity on flow and heat transfer characteristics of unsteady Williamson fluid

Abstract: A two-dimensional mathematical model of magnetized unsteady incompressible Williamson fluid flow over a sensor surface with variable thermal conductivity and exterior squeezing with viscous dissipation effect is investigated, numerically. Present flow model is developed based on the considered flow geometry. Effect of Lorentz forces on flow behaviour is described in terms of magnetic field and which is accounted in momentum equation. Influence of variable thermal conductivity on heat transfer is considered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 53 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…The guarantee of the implemented BVP4C Matlab numerical code is validated by comparing produced similar results with former solutions stated by Khaled and Vafai [28] and Usha et al [42] under squeezing regime for different parameters namely squeezed flow index and Prandtl number for temperature field with absence of magnetic force field. However, Table 1 clearly explores this comparison and this documentation furnishes the higher order confidence in the produced similar results in this investigation.…”
Section: Bvp4c Numerical Code Accuracymentioning
confidence: 58%
See 3 more Smart Citations
“…The guarantee of the implemented BVP4C Matlab numerical code is validated by comparing produced similar results with former solutions stated by Khaled and Vafai [28] and Usha et al [42] under squeezing regime for different parameters namely squeezed flow index and Prandtl number for temperature field with absence of magnetic force field. However, Table 1 clearly explores this comparison and this documentation furnishes the higher order confidence in the produced similar results in this investigation.…”
Section: Bvp4c Numerical Code Accuracymentioning
confidence: 58%
“…Additionally, the š‘„ āˆ’ š‘¦ coordinate system is deployed and in which š‘„-axis is taken along the axial flow direction. Consequently, under the aforementioned closed channel and boundary layer flow predictions and by deploying the suitable equations from the non-Newtonian second-grade fluid model as depicted in Section 2, the governing flow, thermal and mass distributive Navier-Stokes conservative expressions for the flow of magnetic second-grade fluid under suspended channel regime are shown by generalizing the existing studies [28,29,36,[38][39][40]42].…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reddy et al (2020) reported the effect of heat absorption/ generation on MHD Cu-water nanofluid stream above a non-linear shrinking/ stretching sheet. The influence of magnetized variable thermal conductivity on the flow and heat transfer characteristics of an unstable Williamson fluid was studied by Shankar et al (2020). Shateyi and Muzara (2020) studied the unsteady MHD Blasius and Sakiadis flows with variable thermal conductivity in the presence of thermal radiation and viscous dissipation.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%